2007
DOI: 10.4049/jimmunol.179.5.2774
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Signaling Reduces the Severity of Experimental Autoimmune Encephalomyelitis by Controlling the Parenchymal Distribution of Effector and Regulatory T Cells in the Central Nervous System

Abstract: The chemokine receptor CXCR3 promotes the trafficking of activated T and NK cells in response to three ligands, CXCL9, CXCL10, and CXCL11. Although these chemokines are produced in the CNS in multiple sclerosis and experimental autoimmune encephalomyelitis (EAE), their role in the pathogenesis of CNS autoimmunity is unresolved. We examined the function of CXCR3 signaling in EAE using mice that were deficient for CXCR3 (CXCR3−/−). The time to onset and peak disease severity were similar for CXCR3−/− and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
145
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 83 publications
(74 reference statements)
17
145
4
Order By: Relevance
“…Studies using CXCR3-deficient mice have demonstrated that CXC10/CXCR3 interactions reduce the severity of disease in mice with EAE. 61,62 In addition, Elhofy and colleagues 63 have reported that overproduction of the chemokine CCL2 in vivo downregulates Th1 immune responses, resulting in mice with an attenuated form of EAE. Thus, our finding that double-Tg animals overproducing CXCL1 after administration of doxycycline display a milder course of MOG-EAE, compared with single-Tg and wild-type mice, is in line with the wide variety of effects that chemokines might have on CNS inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using CXCR3-deficient mice have demonstrated that CXC10/CXCR3 interactions reduce the severity of disease in mice with EAE. 61,62 In addition, Elhofy and colleagues 63 have reported that overproduction of the chemokine CCL2 in vivo downregulates Th1 immune responses, resulting in mice with an attenuated form of EAE. Thus, our finding that double-Tg animals overproducing CXCL1 after administration of doxycycline display a milder course of MOG-EAE, compared with single-Tg and wild-type mice, is in line with the wide variety of effects that chemokines might have on CNS inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…30 To elucidate the molecule(s) responsible for the altered localization of T reg cells, we next analyzed the expression of chemokine receptors involved in the function of T reg cells [31][32][33][34] by flow cytometry. Both Foxp3 ϩ and Foxp3 Ϫ CD4 ϩ T cells in the spleen showed decreased CCR7 expression ( Figure 4C) and enhanced CXCR4 expression ( Figure 4E) in aged BWF1 mice.…”
Section: Changes In the Expression Of Chemokine Receptors On T Reg Cementioning
confidence: 99%
“…This finding argues for a strong diseasepromoting function of the CXCR3 chemokine system in IL-12-induced neuroinflammation in the GFAP-IL12 model and is in contrast to previous findings in EAE, where CXCR3 has a disease-limiting function independent of the recruitment of effector T cells to the CNS. 24,37 The gross reduction of leukocytes in the parenchyma and subarachnoid space of GF-IL12/CXCR3KO mice provides evidence of a functional role of CXCR3 in mediating the leukocyte accumulation in the CNS as a result of IL-12 overproduction. However, CXCR3 deficiency did not completely prevent cerebellar inflammation in all GF-IL12/CXCR3KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…6,36 In particular, studies of EAE did not reveal the expected diseasepromoting effect of CXCR3 but rather protective and disease-limiting functions. 24,37 We examined the role of CXCR3 in a less complex T H 1-mediated model of spontaneous CNS inflammation in transgenic mice with astrocytetargeted production of IL-12. Within the CNS of these mice with CXCR3 deficiency, we observed a markedly attenuated inflammatory response, which corresponded with the well-characterized impact of the CXCR3 chemokine system on the migration and attraction of type 1 immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation